ASP.NET Web Development with Macromedia Dreamweaver MX 2004 - Hadjisotiriou, Costas (Apress, 2012)
ASP.NET is not only the latest version of Microsoft's Active Server Pages (ASP), it is a whole new programming concept altogether. This incredibly popular server-side scripting language is based on the .NET Framework, and it combines unrivalled developer productivity with performance and reliability.